Exploring social work : an anthropological perspective - Bell, Linda (Associate professor) (Policy Press, 2020)
This unique study of social work provides a bold and challenging view of the subject from an anthropological perspective. Combining research and personal reflection, it explores cultural and symbolic representations of social work, evolving identities of social work practitioners and the ways in which they and society now view one another.